Effect of Growth Parameters and Annealing Atmosphere on the Properties of Cu2ZnSnS4 Thin Films Deposited by Cosputtering. (30th April 2013) - Khalkar, Arun; Lim, Kwang-Soo; Yu, Seong-Man; Patole, Shashikant P.; Yoo, Ji-Beom
Abstract : Cu2 ZnSnS4 (CZTS) thin films were deposited using the cosputtering technique. The growth parameters, such as working pressure, target powers, and postannealing atmosphere, were optimized for CZTS films deposition. A comparative study between post annealing using sulfur vapor in a quartz tube furnace and sulfurization chamber using H2 S gas was carried out to optimize the kesterite Cu2 ZnSnS4 phase. 10 min annealing at 530°C in the furnace in sulfur vapor eliminated all the secondary phases and formed kesterite Cu2 ZnSnS4 . The diffusion of sulfur in the film during the annealing process enhanced the crystallinity of the film. The kesterite Cu2 ZnSnS4 phase was confirmed by X-ray diffraction, Raman scattering, and optical measurements. The film showed phonon peaks corresponding to the kesterite CZTS, high-absorption coefficient (1.1 × 10 5  cm −1 ), and desired optical direct band gap (1.5 eV).